2011
DOI: 10.1126/science.1207325
|View full text |Cite
|
Sign up to set email alerts
|

Images of Asteroid 21 Lutetia: A Remnant Planetesimal from the Early Solar System

Abstract: Images obtained by the Optical, Spectroscopic, and Infrared Remote Imaging System (OSIRIS) cameras onboard the Rosetta spacecraft reveal that asteroid 21 Lutetia has a complex geology and one of the highest asteroid densities measured so far, 3.4 ± 0.3 grams per cubic centimeter. The north pole region is covered by a thick layer of regolith, which is seen to flow in major landslides associated with albedo variation. Its geologically complex surface, ancient surface age, and high density suggest that Lutetia is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
133
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 189 publications
(149 citation statements)
references
References 32 publications
12
133
2
2
Order By: Relevance
“…Most of the data have been acquired at relatively small phase angles, thus we have a good sampling of the opposition surge. If we fit a straight line for the radiance factor of facets observed with phase angle larger than 20 • , we measure a increase of the radiance factor of 0.11 due to the non-linear enhancement, which is ∼ 50% of the albedo at zero phase angle (0.19 ± 0.02, the geometric albedo according to Sierks et al, 2011). The spread of points is due to geometric condition only, the so-called disk profile (Shkuratov et al, 2011), were facets close to limb are obscured in the extreme values of incidence and emergence angles.…”
Section: Then It Providesmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the data have been acquired at relatively small phase angles, thus we have a good sampling of the opposition surge. If we fit a straight line for the radiance factor of facets observed with phase angle larger than 20 • , we measure a increase of the radiance factor of 0.11 due to the non-linear enhancement, which is ∼ 50% of the albedo at zero phase angle (0.19 ± 0.02, the geometric albedo according to Sierks et al, 2011). The spread of points is due to geometric condition only, the so-called disk profile (Shkuratov et al, 2011), were facets close to limb are obscured in the extreme values of incidence and emergence angles.…”
Section: Then It Providesmentioning
confidence: 99%
“…The rotational period of 8.168 hours and direction of the pole axis were improved (Carry et al, 2010). The global shape with principal axes dimensions of 121 ± 1 km × 101 ± 1 km × 75 ± 13 km was determined (Sierks et al, 2011), even if a large fraction of the asteroid's southern hemisphere was not visible during the fly-by and consequently the shortest semi-major dimension is not well constrained. From the shape model, an estimation of volume of (5.0 ± 0.4) · 10 5 km 3 has been derived and combining it with the mass obtained by the Radio science investigation 1.7 · 10 18 kg ± 1 by Pätzold et al (2011) a bulk density of 3.4 ± 0.3g · cm −3 has been computed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rosetta encounter with main-belt asteroid (21) Lutetia has demonstrated that not all M-type asteroids are metal-rich 17 . Indeed, the low radar albedo 8 of 1950 DA is very similar to that of Lutetia, suggesting a similar composition.…”
mentioning
confidence: 99%
“…Indeed, the low radar albedo 8 of 1950 DA is very similar to that of Lutetia, suggesting a similar composition. The best meteorite analog for Lutetia is an enstatite chondrite 17 , which has a grain density of 3.55 g cm -3 . Taking the same meteorite analog and grain density for 1950 DA implies a macro-porosity of 51 ± 19 % and indicates that it is a rubble pile asteroid (Fig.…”
mentioning
confidence: 99%